Influence of metabolic and physical factors on production of diacetoxyscirpenol by Fusarium sambucinum Fuckel. - Monnet, D (1988)
Fusarium sambucinum Fuckel 8099-1 was grown on Czapek-Dox peptone-supplemented medium at 15 degrees C for 14 days, and the cultures were investigated for diacetoxyscirpenol (DAS) production by liquid-liquid extraction and gas chromatography. The addition of 150 mg of sorbic acid, a tricarboxylic acid cycle inhibitor, per liter stimulated both fungal growth and DAS production. Among the beta-hydroxy-beta-methylglutaryl coenzyme A precursors tested, isovaleric acid completely inhibited fungal growth and DAS production, ethyl isovalerate did not support a significant increase in DAS production, and L-leucine partially inhibited DAS production, showing that L-leucine and isovaleric acid catabolisms do not induce trichothecene biosynthesis. Solid particles (cork powder) were necessary for DAS production in stationary cultures but did not influence DAS production in shaken cultures. Shaking strongly stimulated DAS production and fungal growth.